What does it take to revolutionize Chinese diets: Evidence from a choice experiment on urban Chinese consumers - Chen, Kevin Z.; Yu, Luyun; Lin, Wen; Ortega, David L. (Emerald Publishing Limited, 2024)
The purpose is to understand the factors affecting Chinese diet selections and propose strategies for revolutionizing Chinese diets toward healthy ones.This study implemented an online discrete choice experiment to identify the factors affecting diet selections among urban Chinese consumers. Four different diet patterns were used to label each of the product alternatives in the experiment, which varied in taste and cost. Specifically, implying the healthiness and sustainability of a diet, the diet alternatives included the average diet, the Chinese Food Guide Pagoda diet, the EAT-Lancet diet and the Flexitarian diet. Using consumer data from six provincial capital cities, we used random parameter logit models to estimate their preferences.Diet type and diet cost were found to be more important in urban Chinese consumers' diet selections than the ability to customize taste. The average diet, although not healthy and sustainable, was preferred most by respondents, signaling the challenges of shifting the consumer diet in China. Increasing the cost of the average diet can significantly promote sustainable healthy diet choices among urban Chinese residents. In other words, improving the affordability of sustainable healthy diets would have the potential to fuel the diet revolution in China.Instead of choices of a single food item, this paper focused on the individual selection of a diet, where different food products can act as substitutes or as complements for one another. We also proposed a way to assess individual preferences and valuations for several different diets.